Climate finance: Funding sustainable food systems transformation - Díaz-Bonilla, Eugenio; Echeverria, Ruben G. (International Food Policy Research Institute, 2022)
The transformation of food systems is crucial for achieving multiple global objectives, including the climate change mitigation, adaptation, and resilience goals established in the 2015 Paris Agreement. This international treaty committed signatories to “making finance flows consistent with a pathway towards low greenhouse gas emissions and climate-resilient development.” Major global initiatives in 2021, including COP26 and the United Nations Food Systems Summit (UNFSS), have reiterated the Paris Agreement objective of reorienting finance flows and have focused international attention on the critical role of food systems transformation in meeting global climate goals.